Tell Me Lies (Peter Brook, 1968) or How I Learned to Start Worrying about Vietnam - Nicole Cloarec (Revue LISA)
The Vietnam War has been dubbed the world’s first “television war”. No war had been broadcast as widely before, leading to numerous documentaries both during and after the war. Moreover, no war has triggered as much protest from civilians around the world, which also generated a number of films that documented these protest movements. At first sight Tell Me Lies may seem one of them, documenting some of the counterculture movement in the UK at the end of the 1960s. However the film is quite unique in both subject and formal approach. As its subtitle “A film about London” indicates, the film is not so much about Vietnam as about the impact that news and images of a war can have on the lives of ordinary people in a country far removed yet indirectly involved in the conflict. The film’s originality also lies in its kaleidoscopic aesthetics, blending documentary techniques with fiction, the immediacy of newsreels and pieces to camera with musical interludes, staged performances, Brechtian “alienation effects” and self-reflexive comments. Interestingly the film was based on Peter Brook’s own play US (1966), which caused quite a stir among the audience. However, Brook did not want to just ‘adapt’ his play for the screen but wanted to find purely cinematographic devices to achieve the same effect, which he defined as “confrontation”. This paper aims to analyse how Tell Me Lies not only provides a challenging reflection about the power of art and film in particular to represent the horrors of war, but also questions how to mediate the emotional impact that these representations can have.